Thermal field modelling of peripheral bearing plain surface of three-roller cone bit under friction - Дрогомирецький, Я.М.; Василик, А.В.; Довжинський, І.М.; Долгопола, Г.Є. (Problems of Tribology, 2014)
The mathematical model of peripheral bearing plain surface of three-roller cone bit is considered. In doing this it has been supposed that peripheral plain bearing an unlimited body.